Distinct types of VHHs in Alpaca - Wang, Xinhao; Zhang, Lu; Zhang, Yao; Li, Jiaguo; Xu, Wenfeng; Zhu, Weimin (Frontiers in Immunology, 2024)
IntroductionVHHs (VH of heavy-chain-only antibodies) represent a unique alternative to Q7 conventional antibodies because of their smaller size, comparable binding affinity and biophysical properties. MethodIn this study, we systematically analyzed VHH NGS sequences from 22 Alpacas and structure data from public database. ResultsVHHs in Alpaca can be grouped into five main types with multiple distinct sequence and structure features. Based on the existence of hallmark residues in FR2 region, VHHs can be classified into two groups: nonclassical VHHs (without hallmark residues) and classical VHHs (with hallmark residues). Based on VHH hallmark residues at 42 position (IMGT numbering, FR2 region) and number of cysteines, we found that Alpaca classical VHHs can be further separated into three main types: F_C2 VHHs with F (phenylalanine) at position 42 and having 2 cysteines within sequences, Y_C2 VHHs with Y (tyrosine) at position 42 and having 2 cysteines, and F_C4 with F at position 42 and having 4 cysteines. Non-classical VHHs can be further separated into 2 types based on germlines mapped: N_V3 for VHHs mapped to V3 germlines and N_V4 for V4 germlines. Based on whether FR2 residues are involved in binding, two kinds of paratopes can be identified. Different types of VHHs showed distinct associations with these two paratopes and displayed significant differences in paratope size, residue usage and other structure features. DiscussionSuch results will have significant implications in VHH discovery, engine e ring, and design for innovative therapeutics.